Variation in Physico-chemical Characteristics of Wood of Candidate Plus Trees of Shisham (Dalbergia sissoo Roxb.) - Kumar, Rajneesh; Sharma, Kulwant Rai; Gupta, Lalit Mohan (Indian Forester, 2005)
The present studies were conducted on variation in physico-chemical characteristics of wood of candidate plus trees (CPTs) of Sissoo (Dalbergia sissoo). Among different CPTs of Dalbergia sissoo, significant differences were noticed for all the characters except for holocellulose contents. The maximum height and diameter were recorded in Khajjian-1 whereas, the minimum height was observed in Dhaulakuan-l and diameter in Dhartatoh-3. The maximum bark percentage was noticed in Dhartatoh-l and minimum in Raja ka Bagh-1. The maximum sapwood percentage and minimum heartwood percentage was found in Dhaulakuan-l, while the maximum heartwood percentage was noticed in Khajjian-1. Physico-chemical properties of sapwood viz., specific gravity, fibre length, cold water solubility, hot water solubility, alcohol-benzene solubility, lignin content and holocellulose content ranged between 0.5138 - 0.6306,0.93-1.22 mm, 2.25 % (1.50) - 6.75 % (2.60), 3.50 % (1.87) - 9.15 % (3.02), 1.01 % (1.00) - 7.56 % (2.75), 23.90 -30.50 % and 66.00 - 76.55 %, respectively. Physico-chemical properties of heartwood of Dalbergia sissoo CPTs viz., specific gravity, cold water solubility, hot water solubility, alcohol-benzene solubility, lignin content and holocellulose content ranged between 0.5275 - 0.6905, 5.25 % (2.29) - 10.15 % (3.19), 9.15 % (3.02) - 11.55 % (3.40), 6.82 % (2.61) - 10.82 % (3.29),30.50.39.70 % and 62.00 - 70.00 %, respectively.